The worlds religions in figures : an introduction to international religious demography - Johnson, Todd M. (Todd Michael), 1958-; Bellofatto, Gina A. (Chichester, West Sussex, UK : Malden, MA : Wiley-Blackwell, 2013)
Provides an introduction to international religious demography, outlining the challenges in interpreting data on religious adherence, and presents a contemporary portrait of global religious belief. Offers the first comprehensive overview of the field of international religious demography detailing what we know about religious adherents around the world, and how we know it.
Introduction -- Overview. Global religious populations, 1910-2010 -- Regional religious populations, 1910-2010 -- Religious diversity -- Projecting religious populations, 2010-50 -- Data and methods. Defining religion and religious identity -- Religious demography as an emerging discipline -- Major sources and collections of data -- Analyzing data on religion -- Dynamics of change in religious populations -- Case studies. Estimating changes in the global Muslim population -- Factors driving change in the global Muslim population -- Estimating China's religious populations -- Assessing religious populations in the Sudans -- Migration and religious diasporas -- Conclusion -- Appendix -- Glossary -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Religions -- Statistics; RELIGION -- Comparative Religion; RELIGION -- Essays; RELIGION -- Reference; Religions; Religions -- Statistics; Electronic books; Statistics